Plasma-Based Surface Modification of Polydimethylsiloxane for PDMS-PDMS Molding. (3rd April 2012) - Lopera, S.; Mansano, R. D.
Abstract : We present and compare two processes for plasma-based surface modification of Polydimethylsiloxane (PDMS) to achieve the antisticking behavior needed for PDMS-PDMS molding. The studied processes were oxygen plasma activation for vapor phase silanization and plasma polymerization with tetrafluoromethane/hydrogen mixtures under different processing conditions. We analyzed topography changes of the treated surfaces by atomic force microscopy and contact angle measurements. Plasma treatment were conducted in a parallel plate reactive ion etching reactor at a pressure of 300 mTorr, 30 Watts of RF power and a total flow rate of 30 sccm of a gas mixture. We found for both processes that short, low power, treatments are better to create long-term modifications of the chemistry of the polymer surface while longer processes or thicker films tend to degrade faster with the use leaving rough surfaces with higher adherence to the molded material.